2018
DOI: 10.1111/bjh.15092
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators in primary plasma cell leukaemia: a multicentre retrospective study of 117 patients

Abstract: We report a multicentre retrospective study that analysed clinical characteristics and outcomes in 117 patients with primary plasma cell leukaemia (pPCL) treated at the participating institutions between January 2006 and December 2016. The median age at the time of pPCL diagnosis was 61 years. Ninety-eight patients were treated with novel agents, with an overall response rate of 78%. Fifty-five patients (64%) patients underwent upfront autologous stem cell transplantation (ASCT). The median follow-up time was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 25 publications
3
59
0
2
Order By: Relevance
“…The potential mechanisms include protecting circulating tumor cells from attack of host's immune system as well as supporting proliferation of tumor cells [35]. But, contradictorily, in many hematological diseases, patients with low PLT have a poor prognosis, such as Ph-like acute lymphoblastic leukemia [36], hemophagocytic lymphohistiocytosis (HLH) [37], primary plasma cell leukemia (pPCL) [38] and DLBCL [39,40]. Our data demonstrated that PLT≦126.…”
Section: Discussionmentioning
confidence: 80%
“…The potential mechanisms include protecting circulating tumor cells from attack of host's immune system as well as supporting proliferation of tumor cells [35]. But, contradictorily, in many hematological diseases, patients with low PLT have a poor prognosis, such as Ph-like acute lymphoblastic leukemia [36], hemophagocytic lymphohistiocytosis (HLH) [37], primary plasma cell leukemia (pPCL) [38] and DLBCL [39,40]. Our data demonstrated that PLT≦126.…”
Section: Discussionmentioning
confidence: 80%
“…Desde la introducción de la quimioterapia en altas dosis, seguido por trasplante de médula autólogo (TAPH) en pacientes candidatos 23 , se observó una mejoría significativa en la sobrevida de pacientes con mieloma múltiple. Sin embargo, los resultados no son extrapolables a los casos de LCPp, en los que la sobrevida es francamente menor [24][25][26][27][28] . No hay estudios prospectivos fase III, por lo que no existen guías precisas de tratamiento.…”
Section: Discussionunclassified
“…The potential mechanisms include protecting circulating tumor cells from attacking host's immune system as well as supporting proliferation of tumor cells [39]. But, contradictorily, in many hematological diseases, patients with low PLT have a poor prognosis, such as Ph-like acute lymphoblastic leukemia [40], hemophagocytic lymphohistiocytosis (HLH) [41], primary plasma cell leukemia (pPCL) [42] and DLBCL [43,44]. Our data demonstrated that PLT≦126.5×10 9 /L was associated with higher Ann Arbor stage, more extranodal sites, higher LDH, lower WBC.…”
Section: Discussionmentioning
confidence: 99%